Optimizing Corporate Criminal Sanctions in Restoring Environmental Functions: Towards Ecological Justice - Niswan Harefa; Maidin Gultom; Ica Karina; Sahata Manalu; Ariston Bachtiar Limbong (Inovasi Pratama Internasional. Ltd, 2026)
The degradation of environmental functions caused by corporate crime has become a systemic crisis in Indonesia. Criminal sanctions that merely impose fines often fail to restore damaged ecosystems, thereby prolonging ecological injustice. This study aims to formulate an optimization model for corporate criminal sanctions oriented toward genuine environmental restoration and ecological justice. Using a qualitative socio-legal method, the research integrates normative analysis of Law No. 32 of 2009, Supreme Court Regulation No. 13 of 2016, and related jurisprudence with empirical data from 30 final and binding court decisions (2015–2023), in-depth interviews with 15 key informants, and focus group discussions. Data were analyzed through thematic and comparative case analysis. The results reveal that only 16.7% of sanctions imposed a mandatory environmental restoration order, and even these were poorly formulated, with no measurable biological recovery targets or monitoring mechanisms. The optimization model designed consists of five elements: judicial capability building, restructuring restoration clauses in verdicts, embedding scientific advisory panels, establishing an ecological remediation fund sourced from corporate fines, and post-judgment supervision by an independent oversight body. The discussion confirms that without transforming the logic of punishment from a retributive-deterrent paradigm to a restorative-ecological one, sanctions will remain symbolic. The conclusion emphasizes that authentic ecological justice can only be achieved when the restoration of damaged environmental functions becomes the primary yardstick of sanction effectiveness